Effect of the Solvent on the Oxygen Evolution Reaction at the TiO2–Water Interface - Gono, Patrick; Ambrosio, Francesco; Pasquarello, Alfredo (Journal of physical chemistry. C, 2019)
We investigate the solvation effect of water on the overpotentials of the oxygen evolution reaction on rutile TiO2 by applying the thermodynamic integration method on atomistic model interfaces with and without the water molecules. We compare the results at the vacuum interface with the commonly used computational hydrogen electrode method, finding overall good agreement. The effect of the solvent is found to be twofold. First, the explicit treatment of the solvent can lead to equilibrium configurations differing from the relaxed structures without solvent. Second, the overpotentials can be affected by up to 0.5 eV. The energetics are subject to electrostatic effects at the interface rather than to modifications in the hydrogen bond network. These results provide a promising perspective on the use of implicit models for treating the solvent.